The Emergence of Early Pottery in East Asia: New Discoveries and Perspectives - Wang, Lixin; Sebillaud, Pauline (Journal of world prehistory, 2019)
The appearance of the oldest pottery in the world is a major focus of Early Neolithic archaeology. So far, most discoveries of early pottery have occurred in South China, North China, the Russian Far East, Japan and Korea. The discovery of very thick, low-fired, fibre-tempered pottery dated from around 10,000 BP at the Houtaomuga Site, in Jilin Province, fills an important gap in the distribution of early pottery in northeast China. Based on multi-disciplinary research and an important series of dates, this article establishes the chronology of the early pottery remains discovered at the Houtaomuga Site and their morphological and technical characteristics, and sheds light on their function. Finally, the authors compare them to the other early pottery sherds discovered in the surrounding region, and throughout East Asia, in order to discuss the significance of this discovery and its implications for the subsistence mode developed in the northwest of the Jilin Province at the very beginning of the Neolithic.